Modernisasi Alat Tangkap pada Nelayan Bajo (Sebuah Studi pada Nelayan Suku Bajo di Desa Latawe Kabupaten Muna Barat Provinsi Sulawesi Tenggara) - Hamzah, Awaluddin; Mukhtar, Mukhtar; Abdi, Abdi; Gafaruddin, Abdul (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to determine the impact of fisheries modernization on the social structure of Bajo Tribe fishermen. The research was conducted from July to September 2017, in Latawe Village, West Muna Regency. After categorizing, a sample of 100 respondents was obtained; there are 45 boat owner fishermen (ponggawa), 30 local fishermen (mustard), 25 fishermen outside the village. Data analysis was carried out descriptively, namely the development of concepts and gathering facts but did not carry out hypothesis testing, and analyzed the relationship between variables for hypothesis testing using quantitative and qualitative approaches. For primary quantitative data, the processing is carried out using frequency tables and simple cross-tabulations. The results showed that the modernization of fisheries in fishing communities had an impact on various aspects of fishermen's life. The use of each type of facility has consequences or impacts that occur, namely work patterns, social structures and the level of welfare of fishermen